(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
This paper focuses on the Canossa lordship in the late 14th century, and makes the point that, whereas in the high Middle Ages rural lordships were intended by domini as tools to further draw resources from their peasants (in addition to rental fees), at the end of the Middle Ages the relationship between politics and economy turned around, and the economic sphere became instrumental to the preservation of the lords’ ascendancy over their men. Faced with the risk of losing control of their peasants, constantly flattered by other lords or by the city of Reggio, the Canossa preferred to require mild corvèes and manorial aid.